In the Context of Okun Law, the Relationship Between Real Output and Unemployment Rate in Oecd: a Panel Error Correction and Panel Ardl Approaches - Altunöz, Utku (Ekonomika, 2024)
In this paper, the correlation between unemployment rate and real output for OECD countries was analyzed through the application of Okun’s Law and unemployment hysteresis 2007-2022. For this purpose, panel error correction, panel cointegration, ARDL Bounds Test and Granger causality techniques were preferred. In addition, unemployment hysteresis was examined with different panel unit root technique in OECD countries. The findings show that there is a long-term link among the variables, while supporting unemployment hysteresis in most OECD countries. Long-term findings show that Okun’s law is applicable. Causality analysis indicates that there is a one-way and negative relationship towards the unemployment rate. The estimation for the long-run coefficient shows that the increase in growth leads to a decrease in the unemployment rate. Short-term findings also support long-term outcomes.
Keywords: unemployment; output; Okun